Freedom of Labor from Ancient Societies to Modern Times - D. V. Ahmetyanov (Теоретическая и прикладная юриспруденция)
The article describes the history of development of the idea of freedom of labor from the times of existence of the Ancient Eastern states until the moment of origin of the complex of legal rules, which will form the branch of labor law in the future. The specifics of genesis and further evolution of freedom of labor are researched within the framework of the conducted work. In addition, the role of the considered subject and attitude of it in each of the indicated historical periods are characterized. In the conclusion of the article the author formulates the following periodization of the development of the idea of freedom of labor: 1) the period of denial of freedom of labor; 2) the period of contempt for freedom of labor; 3) the period of corporate restrictions on freedom of labor; 4) the period of absolute freedom of labor; 5) the period of rationalization of freedom of labor.